The Effect of Earning and Information Quality on Stock Trading - Abdorreza Asadi; Ahmad Zendehdel; Bibi Zahra Sanagostar (Iranian Journal of Accounting, Auditing & Finance)
This study investigates the effect of earnings and information quality on stock trading. The statistical population consists of 99 listed companies in Tehran Stock Exchange from 2013 to 2018. To test the hypotheses, multiple regression analysis of panel and pool data structure is used. The results show that the earnings persistence, earnings response coefficient, and accruals quality significantly affect the trading days’ ratio. Furthermore, it reveals an insignificant relationship between the annual stock return and trading days’ ratio. The results further reveal that the effect of earnings persistence and quality of accruals on stock trading turnover is similarly insignificant. Simultaneously, the earnings response coefficient and annual stock return significantly affect the stock trading turnover.